POLA HUBUNGAN PEMERINTAH PUSAT DAN DAERAH DALAM PEMANFAATAN RUANG DAN KAWASAN PERTAMBANGAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NO.37/PUU-XIX/2021 - Herawan, Herawan (UNIB Press, 2023)
Law No.3 of 2020 concerning Mineral and Coal has serious problems because it stipulates that the management of mineral and coal resources is under the control of the central government. In the Mineral and Coal Law there is also a division of mining business areas. However, changes in the use of space and mining areas in the Mineral and Coal Law are not explicitly guaranteed. Therefore, the articles governing the use of space and mining areas were subject to material review by the Constitutional Court and in Decision No.37/PUU-XIX/2021 it was stated that the application was partially granted. This research answers 1). How is the dynamics of mining management arrangements in the three laws, and 2). What are the implications of Decision No.37/PUU-XIX/2021 on the dynamics of relations between the central and regional governments. This research is normative research. The results of this study state that there is a provision regarding the guarantee of no utilization of mining space and area from the Central and Regional Governments because the utilization of mining space and area can only be carried out as long as it does not conflict with the laws and regulations. This is guaranteed by the Constitutional Court in its Decision No.37/PUU-XIX/2021.